Risk factors of cardiovascular disease among st-elevation myocardial infarction male patients in Malaysia from 2006 to 2013 - Juhan, Nurliyana; Mohd Khalid, Zarina; Zubairi, Yong Zulina; Mahmood Zuhdi, Ahmad Syadi; Wan Ahmad, Wan Azman (Penerbit UTM Press, 2019)
Cardiovascular disease is the leading cause of death in Malaysia and globally. This study aimed to identify associated risk factors in cardiovascular disease among ST elevation myocardial infarction (STEMI) male patients and obtain a feasible model to describe the data. A total of 16,673 STEMI male patients from 18 participating hospitals across Malaysia in the National Cardiovascular Disease Database-Acute Coronary Syndrome (NCVD-ACS) registry year 2006-2013 were analysed. Univariate analysis was conducted. Significant variables from the univariate analysis were further analysed by a multivariate logistic analysis to identify the prognostic factors. The most prevalent risk factor for male patients was smoking (79.3%), followed by hypertension (54.9%) and diabetes mellitus (40.4%). At univariate level, this study is consistent with the findings from the Malaysian National Health and Morbidity Survey (NHMS) where smoking is a significant risk factor. After adjustment in multivariate logistic model, the risk factors for cardiovascular death among male patients are related to age, premorbid condition such as diabetes mellitus, hypertension, family history of CVD, Killip class, type of treatment such as percutaneous coronary intervention (PCI) and relevant comorbidity such as renal disease. Drastic efforts in the management of all risk factors in males is needed to improve adherence outcomes. © 2019, Penerbit UTM Press. All rights reserved.